Ethanol Effect on the Performance of a Conventional Solar Still - Bellila, A.; Souyei, B.; Kermerchou, I.; Smakdji, N.; Sadoun, A.; Elsharif, N.; Siqueira, A. (ASEAN Journal of Science and Engineering, 2024)
The lack of drinking water is a major problem in many parts of the world, and solar distillation can be an effective solution. Solar distillation is a simple process that uses the energy from the sun to evaporate water and then collect the condensed vapor, leaving behind impurities. Ethanol has a lower boiling point than water, which means it evaporates more easily when exposed to heat. This can improve the efficiency of solar distillation by allowing the water to evaporate more quickly and at a lower temperature, reducing the amount of energy needed from the sun. The results you mentioned, showing a 20% improvement in performance compared to conventional solar stills, are promising. However, specific results and effectiveness of this modification may vary depending on various factors such as the type of still used, the concentration of Ethanol used, and environmental conditions